The missions and missionaries of California - Engelhardt, Zephyrin (James H. Barry, 1915)
v. I. Lower California --v. II. Upper California. pt. I. General history -- v. III. Upper California. pt. II. General history --v. IV. Upper California. pt. III. General history.